X-Ray Fluorescence for Laminated Silty Shale Reservoirs in Ordos Basin, China: Implications for Lithology Identification. (31st July 2022) - Cheng, Wei; Cheng, Hao; Yu, Hongyan; Zhang, Shaohua; Wang, Zhenliang; Li, Xiaolong; Johnson, Lukman
Abstract : Shale lithofacies were an important key for the exploration and development of unconventional oil and gas reservoirs. Previous studies usually use logging data, X-ray diffraction analysis (XRD), and scanning electron microscopy (SEM) to identify shale lithofacies, but these methods cannot accurately and quickly identify geochemical characteristics. Portable X-ray fluorescence (XRF) analysis can identify geochemical characteristics. However, few publications reported the feasibility of XRF identifying lithology. We tested the major elements of this formation systematically by X-ray fluorescence and compared the characteristics of these elements in the silty laminated shales against the calcareous laminated shale and the argillaceous shales. We analyzed the geochemical characteristics of shale using portable XRF and proposed a method to identify argillaceous shale, silty laminated shale, and calcareous laminated shale in the Chang 7 of Well Y1 (in Xiasiwan area). Furthermore, we established a lithoface identification standard. We also found that Ca/Mg of calcareous laminated shale was the highest which indicated a dry depositional environment; in contrast, lowest Ca/Mg of silty laminated shale indicated a humid depositional environment. Argillaceous shale was deposited in a strongly reducing environment because Fe content of argillaceous shale was the highest. Finally, this criterion is tested against the data from the Well Y2, and the results are in good agreement with the thin section analysis and core data.